The Impact of Servant Leadership and Work Environment on Employee Performance with Work Discipline as an Intevening Variable in the KPPU Office - Dedy Djunaedi; Teuku Noerman (East Asian Journal of Multidisciplinary Research, 2024)
Research in this thesis aims to examine how work discipline functions as an intervening variable in the relationship between employee performance and servant leadership with the work environment. Respondent data will use the results of the questionnaire distribution to KPPU Head Office employees who are permanent employees with a minimum service period of 5 years and employee ages between 25 to over 50 years online to 100 employees. Seven tests were conducted in this study on hypotheses based on variable indicators made using the smartPLS approach in the analysis of SEM PLS (Partial Least Square). There are three types of testing in this process: outer model, inner model, and hypothesis. This research is expected to have theoretical and positive consequences associated with the research. In addition, businesses can use the implications of this research to inform the creation of job improvement initiatives for their employees.